PERANAN KREDIT KOPERASI RUMONDANG TERHADAP KESEJAHTERAAN PEGAWAI PT BANK RAKYAT INDONESIA (PERSERO) Tbk CABANG MEDAN - Yusni Margaret; Irsad Lubis (Ekonomi dan Keuangan, 2013)
This study aimed to determine the role and benefits of credit to employee well-being, knowing the background of the cooperative Rumondang borrow, knowing the realization of loans in accordance with the cooperative principles and know the obstacles in obtaining credit in cooperative Rumondang. The data analysis technique used is the analysis of quantitative data and descriptive analysis of formula prepared from primary data through questionnaires and secondary. Based on the result of the study showed that many employees of The Bank Rakyat Indonesia, which received a credit from the cooperative. Filling requirements in the credit cooperatives to be easier and less expensive than the cost of credit to the Bank Rakyat Indonesia. Employees cooperative lending to members at low interest rates could improve the welfare of members because members can meet other needs. Received credit for the development of the majority of members of members. Results of calculations by Trend known that the growing amount of credit received by members of cooperatives in 2004-2011 has increased because of the need to live the higher the gain credit can increase the amount of revenue by a very large loan in improving the welfare of member cooperatives so cooperative Rumondang successfully implements the principles of cooperation in terms of improving the welfare of members.